2012
DOI: 10.1021/nl303820a
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Modulation of the Membrane Potential in Solid-State Ion Channels

Abstract: Biological ion channels are molecular devices that allow a rapid flow of ions across the cell membrane. Normal physiological functions, such as generating action potentials for cell-to-cell communication, are highly dependent on ion channels that can open and close in response to external stimuli for regulating ion permeation. Mimicking these biological functions using synthetic structures is a rapidly progressing yet challenging area. Here we report the electric field modulation of the membrane potential phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 32 publications
4
51
0
1
Order By: Relevance
“…13 Moreover, another pioneering work investigated the ionic response to ac fields. 14 From another perspective, there are many possibilities for constructing narrow channels to obtain various nonlinear ionic transport characteristics. Despite a long history, 1518 however, the relation between the time and spatial scales of the electrical response of ionic solutions at the nanoscale remains unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, another pioneering work investigated the ionic response to ac fields. 14 From another perspective, there are many possibilities for constructing narrow channels to obtain various nonlinear ionic transport characteristics. Despite a long history, 1518 however, the relation between the time and spatial scales of the electrical response of ionic solutions at the nanoscale remains unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane transport experiments in [9] revealed that that the fluxes of anionic and cationic permeate species change as a function of applied potential. The modulation of membrane potential by the external electric field in solid-state channels was also demonstrated in [10], while a significant increase of ionic conductivity in nanopores and nanochannels due to application of a prescribed potential to their conductive surface was reported in [11][12][13].…”
Section: Introductionmentioning
confidence: 89%
“…(14c). The shooting method is used to solve the problem by integrating (14) from z = 0 to z = 1 and matching the hydrostatic pressure, salt concentration and pH in the reservoir connected to the pore exit.…”
Section: Theoretical Modelmentioning
confidence: 99%